ANALISIS MODEL PEMBELAJARAN IPA DI SMP - Izah, Naelatul; Wiyanto, Wiyanto; Handayani, Langlang (UPEJ Unnes Physics Education Journal, 2017)
Learning science is learning that requires teachers to implement various learning models in which are creative, innovative, interesting, fun, effective, and varied so that competence and expectations are able to be accomplished. This research aimed to discover implementation of science learning models in KTSP based and 2013 Curriculum based Junior High Schools. This research used observation method by using video as the tool and questionnaire. The results of this research discovered that students activities in paying attention to teachers in percentage at Junior High School coded A, Junior High School coded B, and Junior High School coded C were at 59,16% 46,06%, 85,80%. In 2013 Curriculum based Junior High School, at Junior High School coded X, Junior High School coded Y, Junior High School coded Z, students activities were representing experiments results, doing experiments,  and doing exercises in which are at 24,50%, 32,78%, and 55,23%. Moreover, the results of questionnaire analysis in Junior High Schools based KTSP were at 76%, 76%, and 72%. Furthermore, in Junior High Schools based Curriculum 2013, were at 88,02%, 84,38%, and 86%.